2017
DOI: 10.1007/s13311-016-0484-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Endpoints in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative, clinically heterogeneous syndrome pathologically overlapping with frontotemporal dementia. To date, therapeutic trials in animal models have not been able to predict treatment response in humans, and the revised ALS Functional Rating Scale, which is based on coarse disability measures, remains the gold-standard measure of disease progression. Advances in neuroimaging have enabled mapping of functional, structural, and molecular aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 135 publications
(141 reference statements)
2
70
0
Order By: Relevance
“…Also diffusion tensor imaging (DTI) findings of reduced white matter integrity in the frontal, temporal and parietal lobes and, often early in the corpus callosum, suggest widespread white matter involvement may underlie both cognitive and other functional changes in ALS 63. These changes are independent of spinal cord pathology.…”
Section: Neurophysiological Considerationsmentioning
confidence: 99%
“…Also diffusion tensor imaging (DTI) findings of reduced white matter integrity in the frontal, temporal and parietal lobes and, often early in the corpus callosum, suggest widespread white matter involvement may underlie both cognitive and other functional changes in ALS 63. These changes are independent of spinal cord pathology.…”
Section: Neurophysiological Considerationsmentioning
confidence: 99%
“…Advances in imaging have led to an increased ability to discern structural changes that make quantitative imaging a powerful outcome measure [3][4][5]. In ALS, quantitative magnetic resonance imaging (MRI) technology can show abnormalities prior to the development of symptoms, and clear changes occur as the disease progresses [4].…”
mentioning
confidence: 99%
“…Menke et al 8 have recently reported imaging abnormalities even before clinical symptoms, offering the potential for neuroprotective intervention, particularly in familial cases. Current literature points to DTI technique as the most promising candidate for imaging biomarker in ALS, able to elucidate the brain phenotype of ALS and also detect white matter tract changes in extramotor regions 8,10 .The results of Chaves et al 11 using a 1.5 Tesla MR equipment reinforce the clinical use of fractional anisotropy (FA) to detect extra-motor brain abnormalities in ALS patients. Despite this further multicenter validation with larger cohorts of patients remains mandatory prior to the integration of this technique into the clinical routine as biomarker able to contribute in standard clinical decision-making algorithms.…”
mentioning
confidence: 99%
“…Menke et al 8 have recently reported imaging abnormalities even before clinical symptoms, offering the potential for neuroprotective intervention, particularly in familial cases. Current literature points to DTI technique as the most promising candidate for imaging biomarker in ALS, able to elucidate the brain phenotype of ALS and also detect white matter tract changes in extramotor regions 8,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation